From melodrama to blockbuster: a comparative analysis of musical camouflage in Victorian theatre and twenty-first-century film. Issue 2 (31st August 2007) - Dean, Rob
This article explores the use of music as a functional device which disguises the artificial construction of narrative media. The identification of the principles behind the specific positioning of musical material in the presentation of film and theatre reveals that in certain scenarios the aural accompaniment is not simply utilized as an emotive tool. Instead the polemic pursued in this article reveals that music also fulfils the practical purpose of camouflaging narrative leaps in time, space and dimension. Furthermore the comparative analysis of nineteenthcentury dramatic texts penned by Dion Boucicault and twenty-first-century films written and directed by M. Night Shyamalan establishes both an interdisciplinary connection between the two media forms and highlights the parallel musical practices employed in the past and the present.